Effects of selenium application concentration, period and method on the selenium content and grain yield of Tartary buckwheat of different varieties. (20th June 2022) - Liu, Panfeng; Song, Lifang; Hao, Shuangnan; Qin, Jie; Yang, Chenbo; Yang, Wude; Feng, Meichen; Zhang, Meijun; Wang, Chao; Song, Xiaoyan
Abstract: BACKGROUND: As a potential selenium‐enriched crop, it is of great significance to study the selenium application of Tartary buckwheat. Therefore, to study the effects of selenium application concentration, variety, selenium application period and method on the grain selenium content and yield of Tartary buckwheat, an orthogonal experimental design was used to carry out field experiments in the Jinzhong and Northwest Shanxi ecological regions at the same time. Heifeng 1 and Jinqiao 2 were applied at the branching stage and flowering stage in the Jinzhong, and Heifeng 1 and Jinqiao 6 were applied at the early flowering stage and peak flowering stage in the Northwest Shanxi with different concentrations of sodium selenite (0, 1.37, 2.74, 5.48, 8.22, 12.33, 18.495, 27.7425 g hm −2 ) by foliar spraying and soil application. RESULTS: The results showed that the selenium content in Tartary buckwheat grains was positively correlated with the selenium application concentration and increased with increasing selenium application concentration, while the yield of Tartary buckwheat first increased and then decreased with the selenium application concentration. The grain selenium content and yield of Tartary buckwheat were affected by the selenium application concentration, variety and application method. CONCLUSION: The most effective selenium biofortification program was spraying 2.32 g hm −2 sodium selenite on the leaves of Heifeng 1 at the early flowering stage in the Jinzhong. In the Northwest Shanxi, spraying 11.01 g hm −2 sodium selenite on the leaves of Jinqiao 6 at the flowering stage was the most effective selenium biofortification program. © 2022 Society of Chemical Industry.